2010
DOI: 10.1074/jbc.m110.134064
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin Regulates Androgen- and Epidermal Growth Factor-induced MAPK Signaling and Cell Proliferation in Prostate Cancer Cells

Abstract: 2 Genomic actions involve binding of androgens to ARs, which then translocate to the nucleus, bind to androgen-response elements, and alter gene expression. In contrast, ARs also induce rapid nongenomic signals that are generally mediated by cross-talk between the AR and either G-proteins or growth factor receptors (1-4). Although transcriptional effects of androgens have been extensively studied, mechanisms regulating nongenomic actions of androgens are poorly understood.One potential regulator of nongenomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 60 publications
(64 reference statements)
6
105
0
1
Order By: Relevance
“…However, PXN was not found to be an independent predictor due to the small number of samples and follow-up time was not long enough. Several studies have shown that PXN plays an important role in regulating tumor cell proliferation and mediating signal transduction of epidermal growth factor (EGF) (2,(10)(11)(12). Various scholars have also demonstrated that PXN leads to resistance to drugs by inhibiting the apoptosis of cancer cells in non-small cell lung cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PXN was not found to be an independent predictor due to the small number of samples and follow-up time was not long enough. Several studies have shown that PXN plays an important role in regulating tumor cell proliferation and mediating signal transduction of epidermal growth factor (EGF) (2,(10)(11)(12). Various scholars have also demonstrated that PXN leads to resistance to drugs by inhibiting the apoptosis of cancer cells in non-small cell lung cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that phosphorylation levels of paxillin (PXN) are related to those of cytokine receptors; the blocking of cell growth factor receptors leads to a compensatory increase in PXN phosphorylation levels, and that PXN plays an important role in mediating signal transduction of the epidermal growth factor (EGF) (2,(10)(11)(12). Therefore, high expression of PXN and increased phosphorylation levels may be one of the reasons for the poor therapeutic effect of cetuximab.…”
Section: Introductionmentioning
confidence: 99%
“…The paxillin homologue leupaxin, a 45 kDa protein with ≈ 37% homology to paxillin, was originally characterized as a multi-functional adaptor protein expressed only in hematopoietic cells [87,[89][90][91]. However, leupaxin, like both Hic-5 and paxillin, has been recently shown to be expressed in a subset of human prostate cancers, accumulating in the nucleus to potentiate androgen receptor (AR) transactivation in a ligand-dependent manner [87,92,93].…”
Section: The Paxillin Superfamilymentioning
confidence: 99%
“…As a possible substitute to HER2, EGFR expression has been documented in 45-70% of TNBCs [169]. Like the HER2 pathway, induction of EGFR by its ligand EGF, has been also been shown to stimulate paxillin serine phosphorylation in a MAPK-dependent manner [170,171].…”
Section: Lmo4 In the Regulation Of This Complex (Unpublished)mentioning
confidence: 99%
“…This was highlighted by the fact that the mutant form of Cat-1 that is defective in its ability to bind paxillin fails to rescue the block on transformation caused by knocking down endogenous Cat-1 in the HeLa cervical carcinoma cells, whereas the expression of a construct that encodes wild-type Cat-1 and is resistant to RNAi restores transformation. Paxillin has been shown in some cases to be required for the growth of cancer cells and transformed fibroblasts (37,38). These studies together with our own lead to the suggestion that the formation of a Cat-1-paxillin complex might recruit or activate a unique set of signaling proteins that stimulate the growth of transformed cells.…”
Section: Discussionmentioning
confidence: 99%